(untitled) (Revista Brasileira de Pesquisa em Educação em Ciências, 2014)
This article highlights how school science pedagogy can be reconceptualized to infuse environmental problem solving and social transformation into a rural community in Malawi. Historically, the environmental education curriculum in the country is teacher-driven and theoretically-oriented, thus offering limited references to the local communities. Through participatory action research, the science teaching and learning practices were reconceptualized to address local environmental challenges. In the process, learners became active agents in the local community to understand and address environmental challenges. By prioritizing environmental issues and concerns within the community through Participatory Rural Appraisal (PRA) tools, the learners facilitated their own learning activities and developed class-community action plans. The ability to take action towards reforestation was empowering to both the students and community members, as the collaborative project demonstrated a community’s ability to identify issues of concern, take action, and work towards the resolution of the issue to improve their environment.